Current possibilities of using materials for temporary closure of burn wound surface - V. Nagaichuk; V. Bihuniak; O. Kravtsov; O. Zhernov; H. Oliinyk (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2022)
The aim of the work was a comparative analysis of clinical effectiveness of existing materials for temporary closure of burn wounds. The advantages of biological wound dressings over gauze or synthetic materials are obvious today. However, the issue of comparing the clinical effectiveness of allo- and xenografts remains debatable. The latter provide rapid reepithelialization, analgesia, wound protection and, as a rule, a favorable treatment outcome. In terms of personal experience, over the past 20 years, with the transition to active surgical tactics for the treatment of patients with burns, enough evidence has been accumulated to confirm the high efficiency of using xenodermografts from domestic pigs to close postoperative wounds. Regarding the advantages of animal derived materials, we can highlight the safety, affordable price, unlimited raw materials for their manufacture, as well as the avoidance of various moral, ethical and legal restrictions. Thus, closure of burn wounds is a major issue in the treatment of thermal injuries, which is especially critical for deep and extensive burns.. Xenoderm grafts of our own design, which are widely used in clinical practice and significantly improve the course of burn disease are among the existing and most effective dressings in Ukraine. No conflict of interests was declared by the authors.